The Effect Of Nutrition Education Using Rotary Wheel Media On Knowledge Of Eating Arrangements In Ssb Athletes - Andita, Puteri Dwi; Sefrina, Linda Riski; Elvandari, Milliyantri (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2025)
Football is a type of sport that is popular among various ages and levels of society. It is very important to pay attention to food management for football athletes, so it is necessary to plan and pay attention to the timing of administration according to the stages of the period, both before, during, and after the match. Knowledge about nutrition is not only crucial for nutritionists but is also important for the wider community, including athletes. This research aims to determine the effect of providing education on athletes' knowledge regarding eating arrangements before competing. The research design used was a quasi-experimental one-group pre and post-test. The population of this study was football athletes at SSB Kancil Mas Karawang, and the total sample was 23 people who were selected using purposive sampling techniques. The research instruments used consisted of a questionnaire, a rotating wheel, a stature meter, and scales. Data analysis used univariate and bivariate analysis with the Wilcoxon statistical test type. The research results show that there is a significant influence of nutrition education on knowledge regarding eating arrangements for SSB Kancilmas Karawang athletes (p < 0.05).